Household Budget Management and Financial Behaviour of the Italian Family in Times of Crisis - Di Maggio, Umberto; Lo Verde, Fabio Massimo (Italian Sociological Review, 2023)
Why are Italians at the bottom of international rankings on financial literacy? Why do they fail to make speculative financial choices and have a marked aptitude for precautionary saving? Using a Weberian perspective on household “budget management” [haushalt] and analysing the results of recent research (e.g. OECD, CONSOB and Bank of Italy), the authors argue that there are always “good reasons” and thus specific rationality that encourages people to save and reject financial speculation. This economic choice emanates from cognitive bias, financial socialisation, financial literacy, and environmental conditions. The hypothesis is that Italian households demonstrate a weaker attitude towards financial speculation and a better tendency to save because they devote more attention to consumption, which, unlike financial investments, increases and strengthens personal well-being and family relational ties. Finally, the authors affirm the social relevance of specific financial rationality, leading to a typical precautionary behaviour toward saving rather than investing. This particular attitude aims to reduce the perception of uncertainty, and this is just what is happening in the current crisis scenario.